2006
DOI: 10.1113/jphysiol.2006.109116
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term reorganization of input‐deprived motor vibrissae representation following motor disconnection in adult rats

Abstract: It has been proposed that abnormal vibrissae input to the motor cortex (M1) mediates short-term cortical reorganization after facial nerve lesion. To test this hypothesis, we cut first the infraorbital nerve (ION cut) and then the facial nerve (VII cut) in order to evaluate M1 reorganization without any aberrant, facial-nerve-lesion-induced sensory feedback. In each animal, M1 output was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…Although the size of the vibrissae representation also increased after limb amputations, the increase was not significant (Sanes et al ., ). Similar to our observations, after complete transection of the facial motor nerve, neighboring representations of the eye/eyelid, neck and forelimb movement regions expand into the de‐efferented whisker representation (Sanes et al ., ; Franchi, ; Franchi & Veronesi, ). Fouad et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although the size of the vibrissae representation also increased after limb amputations, the increase was not significant (Sanes et al ., ). Similar to our observations, after complete transection of the facial motor nerve, neighboring representations of the eye/eyelid, neck and forelimb movement regions expand into the de‐efferented whisker representation (Sanes et al ., ; Franchi, ; Franchi & Veronesi, ). Fouad et al .…”
Section: Discussionmentioning
confidence: 99%
“…What are the mechanisms behind the cortical reorganization? Animal models of cortical map plasticity have shown that the first step in cortical map reorganization is the loss of local interneuron inhibition and the unmasking of pre‐existing horizontal cortical connections under active up and down regulation of local α‐aminobutyric acid‐ and glutamate‐related synaptic function 19, 20. These synaptic changes take place simultaneously to massive local glia cell activation and neural immediate early gene activation known to be related to synaptic remodelling 6, 21.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their importance for animals, 45 whisker movements are a relatively simple form of movement, restricted to a single dimension alone and an area where load plays a minor role. 38 In addition, experimental data suggest that the rhythmic sweeps of the mystacial vibrissae are mainly ballistic, centrally preprogrammed feedback-independent movements 46-49 maintained by a whisking central pattern generator at medullary level. [48][49][50][51] Conversely, the role of perioral muscles in humans is highly voluntary and complex, because it contributes to facial mimicry, language, eating, emotional expression, and other open-loop movements.…”
Section: Similarities and Differences Between Studies Using Bt In Animentioning
confidence: 99%
“…Studies in animals that had facial sensory nerves cut and facial motor nerves lesioned provided evidence that signals starting from peripheral motor structures promote plastic changes in the motor cortex in the absence of sensory input. 38 Transcranial magnetic stimulation studies in humans showed that after partial or total axotomy of the facial nerve, the hemisphere contralateral to the paralytic side reorganizes the corticofugal output by increasing its drive to intact perioral muscles. 39 Hence, severed facial motor function invariably leads to cortical reorganization that is not mediated by sensory changes.…”
Section: Into the Facial Districtmentioning
confidence: 99%